Processes Aaffecting Fate of Toluene During Transport Through Quartz Sand - Chung, S. G.; Kim, D. J.; Choi, J. W.; Lee, S. H. (WILEY-BLACKWELL, 2012)
Biodegradation of organic compounds during transport in aquifer systems has become an important issue in applying bioaugmentation to a target area. In this study, we conducted a set of laboratory column experiments for various patterns of solutes, that is, KCl only, toluene only, toluene and bacterium Pseudomonas putida, to investigate how the processes of sorption, biodegradation, and bacteria affect the fate of toluene during transport through quartz sand. The column experiments revealed that (i) sorption of toluene onto sand occurred irreversibly with a mass loss of 35% without any retardation, (ii) biodegradation also occurred but to a lesser extent (similar to 21%) than the irreversible sorption, and (iii) for the case of toluene and bacterium, a rather long tailing was present in the effluent concentraion curves of bacterium and toluene. The tailing of bacterial curve can be explained by the secondary energy minimum of DLVO theory. The tailing of toluene curve was attributed to the sorption of toluene onto bacterial cells during transport which was evidenced by the separate biosorption test. This implies that sorption does not affect directly the microbial activity, and the bacterium Pseudomonas putida can impact toluene transport positively (mass loss via biodegradation) as well as negatively (mass added via enhancement) upon simultaneous introduction into the aquifer. These results would provide valuable information on the design of bioaugmentation scheme for bioremediation of groundwater contaminated with BTEX compounds.(C) 2011 American Institute of Chemical Engineers Environ Prog, 31: 318-324, 2012